Basel III leverage and capital ratio over the economic cycle in the Czech Republic and its comparison with the CEE region - Karel Janda; Oleg Kravtsov (European Financial and Accounting Journal, 2019)
This paper investigates the implications and effectiveness of Basel III leverage requirements for the banking sector in the Czech Republic and its comparison with the Central and Eastern European (CEE) region. We discuss the relationships between the leverage and capital ratios and analyse their constraining effects and cyclical qualities. The empirical analysis consists of examination of the correlation patterns between the leverage and capital ratio in relation to the changes in the business cycles. We propose an empirical model that allows testing how the leverage ratios and their variables respond to the changes in the economic cycles of the CEE region. The analysis of correlation patterns among the variables suggests that the total assets or exposure in contrast to the Tier 1 capital are the main contributors to the cyclical movements. The regression analysis shows that the leverage ratio in normal times is strongly pro-cyclical to the capital ratio and counter-cyclical in the crisis period. The empirical evidence indicating the active balance sheet management in response to the cyclical changes advocates in favour of constraining regulations on the leverage.
Keywords: G21; G30; G32; 650; Basel III; Capital Ratio; CEE; Czech Republic; Leverage Ratio